Biodegradable synthetic macromolecules as anticancer therapeutics - Tay, Joyce Jia Xin (Nanyang Technological University, 2023)
Synthetic cationic anticancer polymers and peptides have garnered rising attention for advancing cancer treatment beyond the agony caused by drug resistance. These positively charged polymers can electrostatically interact with the negatively charged cancer cell membrane, before translocating across to kill the cancer cells by targeting intracellular proteins and genetic materials. Despite their success in vitro, these highly cationic charged polymers often led to nonspecific interactions with blood components. Therefore, this study could serve as a starting point for the exploration of macromolecules that should remain negative or uncharged in the physiological environment to minimize toxicity and prolong blood circulation time but would activate the cationic charges in tumor tissues and their intracellular compartments to accelerate the cellular uptake and assist the endosomal escape. In Chapter 2, we first explored the structure-anticancer activity relationship of a series of cationic guanidinium-functionalized amphiphilic random copolymers synthesized via organocatalytic ring-opening polymerization (OROP) of various functional cyclic carbonate monomers. The type of comonomer units bearing hydrophobic groups as well as the feed ratio between the two monomers were varied to optimise the polymers’ amphiphilicity. Subsequently, these copolymers were evaluated for their anticancer activity, killing kinetics, degradability and functional mechanism. To maximize treatment efficacy and reduce in vivo toxicity, we reported, in Chapter 3, a self-assembled nanoparticulate delivery system derived from the charge-charge interactions between an anionic pH-sensitive polypeptide (mPEG-b-PLL/DCA) and a cationic anticancer polycarbonate guanidinium-functionalized random and block copolymer (Butyl-Gua). The formation of nano-coacervate (Gua-NPs) neutralized the positive charges of Butyl-Gua, which 2 promoted significant improvement in tumor accumulation and inhibited tumor growth whist imposing minimal side effects in vivo. A combination of passive and active targeting of CD44 receptors were investigated in Chapter 4 for enhanced cellular uptake towards cancer cells to achieve controlled drug release. The sophisticated delivery system comprised of the acid sensitive anionic benzoic acidfunctionalized polycarbonate electrostatically attached to the cationic guanidiniumfunctionalized polymer to form a nanocomplex before being coated with CD44-targeting hyaluronic acid (HA). Upon the receptor-mediated uptake of this Hex_mPEG-BA@HA nanocomplexes, the anticancer agents were released in response to the reducing cellular environment and induce efficient apoptosis. Lastly, this thesis concludes with an evaluation on the usage of synthetic polymeric nanoparticulate system as anticancer therapeutics and discusses possible strategies of using patient-derived cancer cell membrane to enhance selectivity and achieve personalized therapeutics.